Outsmarting cancer : risk reduction and the power of prevention - Barsouk, Adam (Johns Hopkins Press health book., 2026)
Outsmarting Cancer reframes one of the most pressing medical challenges of our how to prevent cancer. In this timely and accessible book, physician and medical researcher Adam Barsouk, MD, presents a sweeping examination of cancer's true origins--biological, environmental, dietary, infectious, industrial, occupational, and behavioral--and makes a compelling case for why cancer prevention must become a central priority in public and personal health.